Fundamentals of antiterrorist policy in democratic regimes - Rivas Nieto, Pedro (Revista de la Facultad de Derecho y Ciencias Políticas, 2007)
Terrorism is one of the major problems that democracies had to face in the last years. From the appearance of international terrorism, democratic regimes have built an effective form of counterterrorism which has managed to support the stability of societies and to guarantee their security. In this article the props, the nature and the effects of counterterrorism are analyzed. At the end, it is possible to affirm that ways employed in the most developed countries of the world to face terrorism have been useful and their employment is recommended.